Pathomorphologic and biochemical studies on experimental sodium toxication in broilers - Eröksüz, H (Scientific Technical Research Council Turkey, 1999)
Pathomorphological and biochemical findings related to experimental sodium toxication were studied. Sixty male chicks were divided into five different groups. Sodium bicarbonate (group-1 and 2) and sodium chloride (group-3 and 4) were added into tap water at 6 and 12 g/l doses, respectively. The chicks in all groups were fed on standart chick and standart broiler ration. Cardiac enlargement and various degree of visceral uricosis were the main macroscopic lesions detected in group-1 and group-2. In group-3 and 4, such macroscopic lesions cardiac enlargement, testicular edema, hemorrhagic gastritis as were detected. Microscopic examinations showed the lesions related to macroscopic ones. The red blood cells, hemoglobine and hematocrite were increased in all experimental groups. Plasma uric acid in group-2 and plasma sodium value in group-4 were increased significantly. The values of right ventricular weight/total ventricular weight and right ventricular weight/total body weight, which are the indication of right ventricular hypertrophy, were increased significantly in group 2 and 4. The occurrence of death in experimental groups began at the 5th week of the experiment. The percentage values of death in groups were 41.7%, 83.3%, 25% and 75%, respectively.
Broyler Piliçlerde Deneysel Sodyum Toksikasyonunda Patomorfolojik ve Biyokimyasal İncelemeler
Keywords: experimental sodium toxication; broiler; pathomorphological and biochemical findings